On Philippine Women at Forty (40’s) - Catalino Noceja Mendoza (Zien Journals, 2021)
Women comprise half of the world’s population; however, this demographic segment remains untapped and, on the large part, discriminated against. In the advent of modern technology, women’s health care in many underdeveloped societies remains untouched. In the aspect of the Filipino views towards health, women seemingly are less priority for health service issues and needs. Factors like the environment; interactions with people, conflict on family relationships, shows to cause conflicts that are projected sometimes in the life of a middle adult woman, particularly upon reaching 40s. In selection with the idea, women who are in their 40s are in greater avenue to experience this diversity, thus further environmental complicities may sit in. In this background, it played a motivational sense to the researcher to gather more information for an in depth analysis, instrumented to facilitate a comprehensive explanation for the underlying concerns of such changes in life to women in their 40s in the Philippines. Health and wellness effects of these changes served to be the baseline inquiry of the researcher for further acquisition of information. Selectively speaking, women found to feel insecurities and worries about the changes they noticed on themselves especially now that they are in their 40s
Keywords: Women; Health and wellness; physical changes